Monitoring Serious Adverse Events in the Sierra Leone Trial to Introduce a Vaccine Against Ebola - Jarrett, Olamide D (J Infect Dis, 2018)
The Sierra Leone Trial to Introduce a Vaccine Against Ebola (STRIVE) was a randomized, controlled trial of rVSVΔG-ZEBOV-GP vaccine in healthcare and frontline workers during the 2014–2016 Ebola epidemic. Overall safety findings have been previously reported; there were no vaccine-related serious adverse events (SAEs). Here we describe the safety monitoring system established for STRIVE and the health conditions that resulted in reported SAEs, as well as factors affecting SAE incidence. Participants were randomized to immediate (≤7 days) or deferred (18–24 weeks later) vaccination and were monitored for safety for 6 months (immediate-vaccinated group) or until vaccination (deferred [unvaccinated] group). Once vaccinated, the latter group was termed crossover-vaccinated and monitored for 6 additional months. Of the 8577 STRIVE participants with safety follow-up data, 4172 were in the immediate-vaccinated group and 4398 were in the unvaccinated group, of whom 3787 received crossover vaccination. Overall, 143 SAEs were reported among 132 participants. Of the 143 SAEs, 130 (90.9%) resulted in hospitalization, and 24 (18.2%) participants with an SAE died. Infections were the most common SAEs; malaria was the most common single diagnosis and the most common cause of death. STRIVE built local capacity for vaccine safety monitoring in future clinical trials and research and in the national immunization program. This information about serious health conditions that resulted in hospitalization or death among a population of relatively young, healthy adults in Sierra Leone could help inform improved delivery of preventive and therapeutic health services. CLINICAL TRIALS REGISTRATION: ClinicalTrials.gov [NCT02378753] and Pan African Clinical Trials Registry [PACTR201502001037220].